Finance Business Planning Over Program after School and Daycare Bunnies - Fifi Fifi; Tantri Yanuar Rahmat Syah; Samerdanta Pusaka; Darmansah Darmansah (Journal of Multidisciplinary Academic, 2019)
The purpose of Bunnies Program After School and Daycare business planning is as a child care agency with an age range about 0 months to 12 years that can help the role of parents in caring and nurturing children by providing the best service to meet customer demand over customer satisfaction. Bunnies Program After School and Daycare business finance planning stages include Profit, Loss, Balance sheet, Cash flow, and Break event point. Strategic location is needed to support this business, the location plan is at the place of residence Scientia Garden Blok O, No.21-23, Boulevard Gading Serpong Street, South Tangerang City, Province Banten.